The Future of the sciences and humanities : four analytical essays and a critical debate on the future of scholastic endeavour - McAllister, James W. (James William), 1962-; Tindemans, Peter A. J., 1947-; Verrijn Stuart, A. A.; Visser, Robert Paul Willem (Amsterdam University Press, 2002)
A discussion of the future of interdisciplinary research.